Perancangan Aplikasi Peminjaman Alat Praktik dengan Verifikasi Foto Berbasis Web pada SMK Media Informatika Jakarta - Dwiatmojo, Satrio; Nuryaman, Yosep (Universitas Batanghari Jambi, 2025)
This study aims to design a web-based application for lending practical tools with photo verification at SMK Media Informatika Jakarta. The design uses the Waterfall software development method and Laravel technology as the main framework. The application testing results were conducted using the Blackbox Testing method, which proved that the designed application has run according to its function at SMK Media Informatika Jakarta.